Firearms and violence in American life—50 years later - Zimring, Franklin E. (Criminology & public policy, 2020)
This article identifies the two key issues in the Firearms and Violence Task Force of the National Commission on the Causes and Prevention of Violence and briefly describes research and policy findings on these questions in the half century since the the report was published. The key issues were the impact of weapon dangerousness on the death rate from violence assault and the positive linkage between increases in civilian gun ownership and increasing use of guns in violence.